Influence of energy and carbohydrate intake on symptoms of overreaching - Halson, S.; Lancaster, G.; Gleeson, M.; Jeukendrup, A. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
Muscle glycogen depletion has been suggested as one possible mechanism for the development of overreaching and overtraining. This study examined the metabolic effects of carbohydrate supplementation on cycling performance during overreaching. Six endurance-trained cyclists completed 4 weeks of training on two occasions, once with high carbohydrate (H-CHO) and once with low CHO (L-CHO) supplementation. Each 4 week period included one week of normal training, one week of intensified training (IT) and 2 weeks of recovery (R). Before IT, after IT and after R each subject performed a constant load test ding which a primed continuous dose of [6,6-2H2]glucose was given to assess glucose kinetics. Performance significantly declined in both trials after IT, however the decline in performance was attenuated during the H-CHO trial (H-CHO:17±3%; L-CHO:26±7%). Submaximal plasma concentrations of cortisol, adrenaline and prolactin were reduced to a greater extent in L-CHO than H-CHO after IT. Rates of appearance and disappearance of [6,6-2H2]glucose were unchanged. Whole-body CHO oxidation was significantly decreased in both trials after IT (p=0.01) and fat oxidation increased in both trials (p=0.01). RER, plasma glucose, lactate and tryglycerides were lower after IT in both trials and glycerol and FFA concentrations were higher after IT in both trials. CHO supplementation did not prevent the development of overreaching, however, it attenuated the resultant decrease in performance and the increase in mood disturbance. Although large changes in substrate oxidation were observed, mechanisms other than glycogen depletion play a role in the development of overreaching. Alterations in hormone profiles are implicated. 75